2010
DOI: 10.1115/1.4001976
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of the Perichondrium to the Structural Mechanical Behavior of the Costal-Cartilage

Abstract: The costal-cartilage in the human ribcage is a composite structure consisting of a cartilage substance surrounded by a fibrous, tendon-like perichondrium. Current computational models of the human ribcage represent the costal-cartilage as a homogeneous material, with no consideration for the mechanical contributions of the perichondrium. This study sought to investigate the role of the perichondrium in the structural mechanical behavior of the costal-cartilage. Twenty-two specimens of postmortem human costal-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 9 publications
0
30
1
Order By: Relevance
“…6) and even 6 V, when a temperature increase of $10 C was observed. This observed stability could also be the product of each auricular sample's intact perichondrium, a dense, fibrous tissue shown to significantly contribute to the tensile mechanical properties of both septal and costal cartilage under these measurement conditions [22,23]. Other differences between elastic and hyaline cartilage contributing to the chemical differences between the two types may include the increased glycosaminoglycan (GAG) content and permeability of septal cartilage, [24] which may have influenced the EMR reactions, though we suspect these subtle differences to have little impact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6) and even 6 V, when a temperature increase of $10 C was observed. This observed stability could also be the product of each auricular sample's intact perichondrium, a dense, fibrous tissue shown to significantly contribute to the tensile mechanical properties of both septal and costal cartilage under these measurement conditions [22,23]. Other differences between elastic and hyaline cartilage contributing to the chemical differences between the two types may include the increased glycosaminoglycan (GAG) content and permeability of septal cartilage, [24] which may have influenced the EMR reactions, though we suspect these subtle differences to have little impact.…”
Section: Discussionmentioning
confidence: 99%
“…Two electrode configurations for EMR have been studied: surface and needle electrodes ( Fig. 1(b)) [9][10][11]23]. Although negligible heat generation has been demonstrated in previous studies [9], other potential compromises to native tissue properties related to EMR are present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary conditions chosen for this study were the same as those used by Forman et al (2010), and the impetus for these boundary conditions is described in detail therein. The whole cartilage segments were tested by displacing the sternal boundary posteriorly (in the x-direction), holding all other boundary degrees of freedom fixed (Fig.…”
Section: Structural Testsmentioning
confidence: 99%
“…First, what is commonly termed the ''costal cartilage'' is actually a composite structure composed of an inner cylinder of hyaline cartilage surrounded by a thick layer of fibrous perichondrium. In a series of structural tests with the perichondrium intact and with the perichondrium removed, Forman et al (2010) demonstrated that the perichondrium contributes an average of 50% of the structural stiffness of the costal cartilage in certain loading modes.…”
Section: Introductionmentioning
confidence: 99%